Postgraduate specialist medical training in Anaesthesiology & intensive care in Estonia - Kruusat, Rein; Karjagin, Juri (Journal of the Portuguese Society of Anesthesiology, 2024)
No presente artigo descreve-se p programa de formação especializada em Anestesiologia e Reanimação da Estónia